Incidence of art. 149.1.8ª of the Constitution in Chapter V of the Preliminary Title of the Civil Code - Font i Segura, Albert (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
The paper examines the impact of Article 149.1.8 of the Spanish Constitution on Chapter V of the Preliminary Title of the Civil Code, exploring how the Constitution transformed Spain’s territorial model from a unitary state to a composite one. Article 149.1.8 CE symbolizes the tensions between unity and legal diversity. The plurilegislative model covered by the Constitution, a product of history and a democratic necessity, should reflect an active acknowledgment of territorial diversity. The text addresses the interpretative challenges posed by the article, particularly concerning the limits of regional competence in civil law and the historical influence on the allocation of powers. It also analyzes how the Constitutional Court has oscillated between foralist and autonomist interpretations. Finally, it reflects on how civil plurilegislation, far from fragmenting the legal system, enriches it by ensuring unity under the principles of constitutional supremacy and legislative plurality.